Pemanfaatan Limbah Bunga Canang Sebagai Sumber Warna Alam : Natural Dyes - Suryawan I Made; Sumantra I Made; Karuni Ni Kadek (Hastagina : Jurnal Kriya Seni, 2026)
Bali, as a major tourist destination in Indonesia, boasts a rich cultural heritage and rich religious traditions, one of which is the use of canang (a kind of sacred offering) as a means of worship for Balinese Hindus. Canang, a sacred offering made from flowers, leaves, and other natural materials, is used daily in various religious ceremonies. However, the high use of canang generates large amounts of organic waste, which has not been optimally managed. The accumulation of canang waste not only pollutes the environment but also contributes to Bali's waste management crisis. However, flower waste from canang has significant potential as a raw material for natural dyes. The natural pigments in flowers can be utilized to produce environmentally friendly and skin-safe natural colors, particularly in ecoprinting. Through the MBKM Program at PT Bali Karya Kreatif, a local business focused on sustainable textile products utilizing natural materials to produce natural dyes, the internship method used is collaborative. This method was chosen because it encourages students to actively engage in interactions, discussions, and collaboration with PT Bali Karya Kreatif to help each other solve problems and achieve shared learning goals. This activity aims to explore the process of processing canang flower waste into natural dyes and its application in ecoprinting techniques on RB 1 rayon fabric. The expected result is a textile product that not only has aesthetic value but also elevates environmental sustainability and local cultural preservation. With this approach, canang waste can be transformed from trash into a creative resource with high economic value.